1999
DOI: 10.1139/y99-096
|View full text |Cite
|
Sign up to set email alerts
|

Human hypoxic ventilatory response with blood dopamine content under intermittent hypoxic training

Abstract: Adaptation to intermittent hypoxia can enhance a hypoxic ventilatory response (HVR) in healthy humans. Naturally occurring oscillations in blood dopamine (DA) level may modulate these responses. We have measured ventilatory response to hypoxia relative to blood DA concentration and its precursor DOPA before and after a 2-week course of intermittent hypoxic training (IHT). Eighteen healthy male subjects (mean 22.8+/-2.1 years old) participated in the study. HVRs to isocapnic, progressive, hypoxic rebreathing we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
3
29
1
Order By: Relevance
“…The repeated daily exposures to hypoxia produced a marked enhancement of the initial ventilatory response to hypoxia by the end of the 14 days, a finding similar to that of others using a variety of repeated exposure protocols (Levine et al 1992;Savourey et al 1996;Katayama et al 1998;Serebrovskaya et al 1999;Garcia et al 2000b). We also observed that during each 20 min exposure to hypoxia the ventilatory response declined slowly, again a finding similar to that of others (e.g.…”
Section: Changes In Chemoreflex Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…The repeated daily exposures to hypoxia produced a marked enhancement of the initial ventilatory response to hypoxia by the end of the 14 days, a finding similar to that of others using a variety of repeated exposure protocols (Levine et al 1992;Savourey et al 1996;Katayama et al 1998;Serebrovskaya et al 1999;Garcia et al 2000b). We also observed that during each 20 min exposure to hypoxia the ventilatory response declined slowly, again a finding similar to that of others (e.g.…”
Section: Changes In Chemoreflex Characteristicssupporting
confidence: 90%
“…For the second type, involving daily exposures to hypoxia, several studies in humans have demonstrated that the initial ventilatory response to hypoxia is enhanced (Levine et al 1992;Savourey et al 1996;Katayama et al 1998;Serebrovskaya et al 1999;Garcia et al 2000b). Most of these studies involved subjects spending time in hypobaric chambers at simulated altitudes: 30 min daily for 6 days at 4 500 m (Katayama et al 1998) or 8 h daily for 5 days, day 1 at 4500 m, day 5 at 8500 m (Savourey et al 1996), or 45 min daily for 5 days week _1 for 5 weeks (Levine et al 1992), with the latter complicated by exercise during the exposures.…”
Section: Repeated Hypoxic Exposures Change Respiratory Chemoreflex Comentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is similar to results from studies of intermittent hypoxia "training" in human subjects. Serebrovskaya et al (1999) report that three hypoxic episodes (7-8%) of 5-6 min for 14 consecutive days in humans increased the ventilatory response to moderate (increased by 96% at 45 mmHg), but not mild (70 -80 mmHg) hypoxia. Thus, intermittent hypoxia augments both short-term hypoxic ventilatory and phrenic responses, but only during moderate to severe hypoxia.…”
Section: Short-term Hypoxic Phrenic Responsementioning
confidence: 90%
“…Exposure of animals and human beings to hypoxia increases both plasma and brain levels of dopamine [34,43]. Ventilatory responses to hypoxia may be modulated by dopamine acting on dopaminergic receptors divided into D1-like (D1 and D5) and D2-like (D2, D3 and D4) subtypes [28].…”
Section: Introductionmentioning
confidence: 99%